PELAKSANAAN DASAR SEKURITI MAKANAN DI MALAYSIA : KAJIAN DARIPADA PERSPEKTIF EKONOMI ISLAM: The Implementation of Food Security Policy in Malaysia: A Study from an Islamic Economics Perspective - Mohd Aris, Noorfazreen; Ab Rahman, Asmak (Jurnal Syariah, 2011)
Food is crucial to all humankind and to obtain an adequate food supply it must either be produced or imported from other countries. This article will discuss the policy that has been implemented by the Malaysian Government in order to ensure an adequate supply of food in Malaysia, namely, the National Agricultural Policy 1984-2010. From an Islamic perspective, this policy is very important for the government to provide direction to the country’s agriculture to ensure it follows the right path in supplying food to fulfil the need of the people. With the implementation of these policies it is clear that Malaysia has food sufficiency for certain foods such as fruits, vegetables, fish, eggs and poultry but still lacks rice, milk and meat.